Consequences of Repetitive Head-Impact Exposure in Sports - literature review - Gajek-Flanczewska, Wiktoria; Flanczewski, Sebastian; Wirkijowska, Małgorzata; Wójtowicz, Katarzyna; Wirkijowski, Jakub; Walczak, Agata; Woźniak, Paulina; Wietrzykowska, Ewa; Sobolewska, Dominika; Michalczyk-Fraszka, Katarzyna; Śliwińska, Martyna; Podraza, Anna (Quality in Sport, 2025)
Repetitive head impacts (RHIs), common in contact sports, have raised concerns about their long-term effects on brain health, potentially leading to conditions like concussions, Chronic Traumatic Encephalopathy (CTE), and other neurodegenerative diseases. CTE, a progressive tauopathy, is associated with cognitive and psychological symptoms, including memory loss and depression. While RHIs have been linked to brain changes such as white matter thinning, the mechanisms behind these changes remain unclear. This article reviews the biophysical mechanisms of concussions, the risks of CTE and chronic neurocognitive impairment (CNI), and the challenges in diagnosing and managing these conditions. It also explores gender differences in concussion incidence and recovery. The review emphasizes the need for better diagnostic tools, injury prevention strategies, and patient-centered decision-making to protect athletes.